(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the role of historical science in the study of environmental policy processes in the context of world politics and diplomacy. International relations, which are increasingly forced to proceed from environmental realities, are a modern truth dictated by external climatic factors. The course of development of this type of transnational relations creates a new historical stage in world diplomacy